COVID-19 Pandemic and Global Corporate CDS Spreads - Hasan, Iftekhar; Marra, Miriam; To, Thomas Y.; Wu, Eliza; Zhang, Gaiyan (Journal of Banking & Finance, 2023)
We examine the impact of the COVID-19 pandemic on the credit risk of companies around the world. We find that increased infection rates affect firms more adversely as reflected by the wider increase in their credit default swap (CDS) spreads if they are larger, more leveraged, closer to default, have worse governance and more limited stakeholder engagement, and operate in more highly exposed industries. We observe that country-level determinants such as GDP, political stability, foreign direct investment, and commitment to crisis management (income support, health and lockdown policies) also affect the sensitivity of CDS spreads to COVID-19 infection rates. A negative amplification effect exists for firms with high default probability in countries with fiscal constraints. A direct comparison between global CDS and stock markets reveals that the CDS market prices in a distinct set of corporate traits and government policies in pandemic times.